Alternative Care For Children In Indonesia: Assessment Practices In A Cirebon Regency Welfare Institution - Ellya Susilowati; Mira Azzasyofia; Ananta Firdaus (Asean Social Work Journal, 2026)
Alternative care for children, such as residential or institutional care, is recognised internationally as a measure of last resort, to be used only when family-based care is unavailable or unsafe. In this context, conducting comprehensive and rights-based child assessments is critical to ensuring children’s best interests are met before, during, and after placement. In Indonesia, the importance of such assessments has been formally acknowledged through the Ministry of Social Affairs Regulation No. 30/HUK/2011 on National Standards of Child Care in Child Welfare Institutions (Lembaga Kesejahteraan Sosial Anak, or LKSA). This study examines the implementation of those standards in practice, focusing on LKSAs in Cirebon Regency. Using a mixed-methods approach, data were collected through an online survey of 24 LKSA’s, interviews with institutional staff and five children, focus group discussions (FGDs) involving stakeholders such as social workers, LKSA managers, and Social Affairs Office staff, and a document analysis of child assessment records. The findings reveal that most LKSAs have not yet implemented assessments effectively in the initial, follow-up, or developmental stages. This lack of systematic assessment affects the quality of care and institutional accountability. The study argues that child assessments must not be reduced to administrative procedures. Instead, they should be involved in identifying individual needs, planning appropriate interventions, and protecting children’s rights. A rights-based, continuous, and participatory assessment process and strengthened social worker competencies are essential to improving the quality and effectiveness of alternative care services for children in Indonesia.